Penerapan Pendekatan Pembelajaran Scientific (Scientific Approach) untuk Meningkatkan Hasil Belajar Siswa Kelas XI IPA2 pada Materi Hidrokarbon di SMA Negeri 9 Tunas Bangsa Banda Aceh - Nuhari, Insan; Nur Adiska, Desi; Rahmi, Rauzatur; Mahyuna,; Nurmasyitah, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Research has been conducted entitled "Application of the Scientific Learning Approach to Improve the Learning Outcomes of Class XI IPA2 Students on Hydrocarbon Material at SMA Negeri 9 Tunas Bangsa Banda Aceh". This research aims to improve student learning outcomes, student activities and determine student responses. The subjects of this research were students of SMA Negeri 9 Banda Aceh in class XI IPA2, totaling 30 students consisting of 17 male students and 13 female students. This type of research is qualitative descriptive research. To determine student learning outcomes on hydrocarbon material, a post-test was carried out at the end of the lesson, observation of student activity through student activity observation sheets and student responses obtained through questionnaires. Based on the research results, the completeness of student learning outcomes through post test questions at the end of learning using a scientific learning approach (scientific approach) on hydrocarbon material was 86.66%, compared to the results before the learning process started, namely 36.6%, so it can be concluded that the application of a scientific learning approach (Scientific Approach) is able to improve learning outcomes. Student activities have also shown an individual level of completion, namely 86.60%. In general, students have followed learning procedures well and provided good overall responses, positive student responses were 95.83% and negative student responses were 4.17%.